2015
DOI: 10.1002/hep.28132
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and liver diseases

Abstract: Regular physical activity beneficially impacts the risk of onset and progression of several chronic diseases. However, research regarding the effects of exercising on chronic liver diseases is relatively recent. Most researchers focused on nonalcoholic fatty liver disease (NAFLD), in which increasing clinical and experimental data indicate that skeletal muscle crosstalking to the adipose tissue and the liver regulates intrahepatic fat storage. In this setting, physical activity is considered to be required in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
150
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(157 citation statements)
references
References 65 publications
(121 reference statements)
4
150
0
3
Order By: Relevance
“…In contrast to the findings of Perri, [72] many study participants in this trial reported at the end of the study, that they struggled with the integration of the demanding volume in the second half of the intervention. Berzagotti (2016) summarized the beneficial effects of exercise on the health of NAFLD patients, but also discuss high dropout rates in physical activity trials in these patients [3]. There is an urgent need to counteract with the sedentary habits of NAFLD patients.…”
Section: The Importance Of Regular Supportmentioning
confidence: 99%
“…In contrast to the findings of Perri, [72] many study participants in this trial reported at the end of the study, that they struggled with the integration of the demanding volume in the second half of the intervention. Berzagotti (2016) summarized the beneficial effects of exercise on the health of NAFLD patients, but also discuss high dropout rates in physical activity trials in these patients [3]. There is an urgent need to counteract with the sedentary habits of NAFLD patients.…”
Section: The Importance Of Regular Supportmentioning
confidence: 99%
“…The available evidence to date suggests a benefit of exercise to decrease fatty liver in NAFLD [13][14][15][16]23], and the question of the optimum prescribed 'dose' of exercise for all liver diseases [14] and the effect of aerobic exercise on liver fat [24] have recently been examined. These analyses show that it remains uncertain as to what exercise should be advised and how intense (and for how long), that exercise needs to be, in order to influence liver fat.…”
Section: Interestingly For Both Incident Fatty Liver (Supplementarymentioning
confidence: 99%
“…In short duration studies, lifestyle changes that have focussed on diet and exercise modification have shown promise in decreasing liver fat as a manifestation of early disease in NAFLD [13][14][15][16]. However, guidelines from Specialist societies regarding recommendations for amounts and intensity of exercise/physical activity in NAFLD are variable.…”
Section: Introductionmentioning
confidence: 99%
“…The systemic role of muscle tissue is strengthened by the large system of hormones, chemokines and other mediators that constitute a dense network of communication between the skeletal muscle and the liver (1,2). This, associated with the evidence of a progressive malnutrition and depletion of muscle mass in end-stage liver disease (ESLD) patients, has led many to study the role of sarcopenia and its systemic effects in this setting, and to identify it as critical risk factor for post-liver transplantation (LT) mortality (3)(4)(5).…”
mentioning
confidence: 99%
“…Post-LT physical activity should be aimed at restoring muscle tone, increased aerobic capacity, reducing obesity and insulin resistance and, ultimately, counteracting the effects of the accumulation of visceral adipose tissue and intrahepatic fat (1). The effect of sarcopenia pre-and post-LT in defining the outcomes of transplantation has been established, as has the need to correct it with nutritional and rehabilitative interventions.…”
mentioning
confidence: 99%